2005
DOI: 10.1098/rspb.2004.2954
|View full text |Cite
|
Sign up to set email alerts
|

Red deer stags use formants as assessment cues during intrasexual agonistic interactions

Abstract: While vocal tract resonances or formants are key acoustic parameters that define differences between phonemes in human speech, little is known about their function in animal communication. Here, we used playback experiments to present red deer stags with re-synthesized vocalizations in which formant frequencies were systematically altered to simulate callers of different body sizes. In response to stimuli where lower formants indicated callers with longer vocal tracts, stags were more attentive, replied with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
274
3
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 291 publications
(291 citation statements)
references
References 25 publications
12
274
3
2
Order By: Relevance
“…However, another effect of a lowered larynx is to increase the length of the vocal tract that causes a decrease of formant frequencies. This in turn can be used to exaggerate size, and playback experiments in red deer which possess a lowered larynx too, have shown that stags respond more to roars with lower formant frequencies compared to roars with higher formant frequencies (Reby et al 2005). In humans, formant frequencies are used to correctly estimate age (Collins 2000) and they strongly influence the The difference between the fundamental frequency and the first formant (in Bark) is plotted against the difference between the first and the second formant (in Bark) for all recordings used in the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…However, another effect of a lowered larynx is to increase the length of the vocal tract that causes a decrease of formant frequencies. This in turn can be used to exaggerate size, and playback experiments in red deer which possess a lowered larynx too, have shown that stags respond more to roars with lower formant frequencies compared to roars with higher formant frequencies (Reby et al 2005). In humans, formant frequencies are used to correctly estimate age (Collins 2000) and they strongly influence the The difference between the fundamental frequency and the first formant (in Bark) is plotted against the difference between the first and the second formant (in Bark) for all recordings used in the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomy of the vocal tract influences the acoustic structure of vocalizations in a variety of species (Fitch 1997;Reby et al 2005;Gamba and Giacoma 2006;Charlton et al 2009). For example, in rhesus macaques (Macaca mulatta) formant frequency dispersion is correlated with vocal tract length and body size (Fitch 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, numerous other non-human animals spontaneously respond to formant shifts in their own species-typical vocalisations (Fitch and Kelley, 2000;Reby et al, 2005;Fitch and Fritz, 2006;Charlton et al, 2007a;Charlton et al, 2008;Charlton et al, 2010; and are capable of perceiving formant shifts in human speech sounds with a high degree of accuracy (Baru, 1975;Burdick and Miller, 1975;Hienz et al, 1981;Hienz and Brady, 1988;Sinnott, 1989;Dooling and Brown, 1990;Sinnott and Kreiter, 1991;Sommers et al, 1992;Hienz et al, 1996). It is also noteworthy that the inter-individual variation in formant spacing we report is high: the minimum and maximum formant frequency spacing values for the exhalation, initial inhalation and later inhalation phases of bellows corresponded to a 16%, 25% and 31% variation around the mean values of 796, 708 and 354Hz, respectively (see Table1).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly though, males rarely engage in direct physical confrontations for access to females (Mitchell, 1990). Accordingly, if size-related information is present in male koala bellows then it could be a key mediator of male reproductive success, allowing males to assess rivals and females to select larger males as mating partners (Reby et al, 2005;Charlton et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%